Regarding us [videorecording (DVD)] - Grey, Alexandra, 1991-; Beck, David; Bobbi, Jennifer; Hawk, Abigail; Curtin, Catherine; Moran, Jacob (Gravitas Ventures, 2025)
After losing her teaching career in the Catholic school system, a transgender woman has a profound impact on the lives of two children, one with two fathers in marital strife, and the other a recent transplant from a conservative household.